THE IMPACT OF PERITONEAL DIALYSIS ON THE FAMILY LIFE OF CHILDREN WITH CHRONIC KIDNEY DISEASE - Lomba, Maria de Lurdes Lopes de Freitas (2015)
Introduction: The pressure ulcers are a public health problem and an indicator of the poor quality of care. This issue is consensual in adults but not recognized in pediatrics. Although it is considered rare, existing studies prove otherwise. Materials and methods: An integrative review of literature was conducted online using CINAHL, Academic Search Complete and Elsevier Science database and selecting the studies that identified the most frequent anatomical locations of pressure ulcers in pediatrics and the more effective preventive measures. A research from the references of the selected studies was added. From the evaluation of the results, 5 studies were selected: 3 address the most common anatomical locations and 2 focus on effective preventive measures. Results: The most mentioned anatomical sites are the occipital and the sacrococcygeal, existing some discrepancy between authors. Despite the lack of studies about the efficacy of the materials and the measures focusing mainly in adults, the most effective preventive measures selected are the nutritional appointments, alternance of decubitus, use of cushions to relieve the pressure, having suitable surfaces and applying gel plates. Discussion and Conclusions: Studies reveal a disagreement about the most frequent sites of pressure ulcers which is justified by the anatomical differences among children and the changes in the pressure locations according to their growth. There is also a dearth of empirical evidence about the effectiveness of the preventive measures. Being vital the recognition of this issue in pediatrics, further investigation is suggested. THE IMPACT OF PERITONEAL DIALYSIS ON THE FAMILY LIFE OF CHILDREN WITH CHRONIC KIDNEY DISEASE Background: Children with chronic kidney disease and their families have to deal, on a daily basis, with various medical procedures and a life of uncertainty. Renal replacement therapy with dialysis and kidney transplantation made survival possible, but caring for these children is complex, with a great impact on family's well-being and life quality. Aim: Identifying the difficulties felt by the parents/care providers, while taking care of the child on peritoneal dialysis, and the strategies adopted by nurses to minimize these difficulties. Method/design: Systematic review of literature without meta-analysis study carried through an on-line literature research from different search engines and databases. 7 articles were selected to build up the research sample: 5 from MEDLINE with Full Text and 2 from CINHAL Plus with Full Text. Results: The family dynamics is negatively affected by the changes imposed from the disease. Parents and particularly the mothers are the main care providers for these children and the greatest difficulties mentioned are maintaining a steady employment and the financial constraints regarding the unemployment status and the increased costs of looking after a peritoneal dialysis dependent child. Although none of these articles focus on results from the implementation of specific nurse interventions, they suggest that the nurse's role is to identify the family's main difficulties, to facilitate the adaptation process and to develop interventions that promote the family's biological, emotional, physical and spiritual well-being.